Professional practice Loma de San Pedro School - Avendaño González, Yaritza L. (David, Panamá : UDELAS, 2010)
Professional practice mau represent a valuable and important experience for students from the educational point of view as to face the reality that involves the exercise of it, significantly enriches the future professional; you can complement the knowledge and develop practical skills, values and attitudes acquiried during their training.
General index Thught Dedication Acknowledgment General index Charts index Graphics index Introduction Chapter I Professional practice report Chapter 2 Teacher's intervention in educational practice 2.1. Framework of reference 2.1.1. Definition 2.1.2. Method 2.1.3. Techniques 2.1.4. Activities 2.1.5. Creativity Chapter 3 Analysis of the professional practice Chapter 4 Title of the proposal Conclusion Recommendation References Annex
Incluye General index
Documento presentado para optar por el título de Licenciatura en Docencia en Ingles
Incluye Bibliografía
No se presta a domicilio
No se saca fotocopia
Keywords: ENGLISH -- INFORME DE PRACTICA DE LICENCIATURA -- TEACHING; SPECIAL EDUCATION FACULTY; SCHOOL OF ENGLISH; LOMA DE SAN PEDRO SCHOOL